Antioxidant and Antimicrobial Activity of Ophiurasaponin Extracted from Ophiopholis mirabilis - Rongzhen Wang; Xiaoyu Xue; Jingrong Zhen; Chenghua Guo (Journal of Chemistry)
The aim of this study was to analyze antioxidant and antimicrobial activity of ophiurasaponin extracted from Ophiopholis mirabilis (overall). Ophiurasaponin was extracted with solvent extraction and purified through AB-8 macroporous resin, silica gel column chromatography, Sephadex LH-20 gel column chromatography, and C18 ODS column chromatography. The antioxidant activity of ophiurasaponin was detected by the chemiluminescence assay. The paper filtering method and the modified agar dilution method were used to determine antimicrobial activity. The results showed that the content of crude ophiurasaponin and the refined ophiurasaponin was 46.75% and 96.72%, respectively. The values of the IC50 of hydroxyl-radicals, superoxide anions, and peroxide were 25.54 mg/mL, 9.98 mg/mL, and 1.37 mg/mL, respectively. The refined ophiurasaponin had a good inhibitory effect on Escherichia coli, Bacillus subtilis, Staphylococcus aureus, Aerobacter aerogenes, and Proteusbacillus vulgaris, and the minimum inhibitory concentration (MIC) was 0.0443 mg/mL. In conclusion, ophiurasaponin from Ophiopholis mirabilis had obvious antioxidant activities and antimicrobial activities which could provide the theoretical basis for further research and development of antioxidant and antimicrobial marine drugs.